Desenvolvimento de novos marcadores microssatélites para Baccharis dracunculifolia (Asteraceae) utilizando Next-Generation Sequencing - Heloiza Navarro de Novaes (2017)
Microsatellite markers are highly mutable and, as a result, demonstrate hypervariability in species and populations. The development of microsatellite markers, which has always been considered a laborious and expensive task, has been transformed by the Next Generation Sequencing (NGS) technology that allows a faster and less costly identification of a large number of loci in non-model organisms for ecological and evolutionary studies. In natural plant populations, identifying ecologically important genetic variants linked to climate, or other selection pressures, is possible with genomic population analysis and maintaining intrapopulation genetic diversity can maximize the potential of a species to resist and adapt to environmental change. Baccharis dracunculifolia DC. (Asteraceae) is a shrub distributed across southeastern and southern South America, is relatively well studied from an ecological perspective and has pharmacological importance. Therefore, given the role of B. dracunculifolia as a key species in the natural succession of endangered ecosystems such as the rupestrian grasslands, its wide distribution in South America and its medicinal and industrial properties, this work aimed to increase the number of microsatellite markers currently available for B. dracunculifolia, representing a molecular tool capable of generating knowledge about the patterns of genetic diversity of this species, potentially providing information of relevance for conservation strategies. Amplification of the markers developed in the genomic DNA of the congeneric species Baccharis concinna and Baccharis aphylla was also evaluated. The sequences generated on the Illumina MiSeq platform were used to identify potentially amplifiable loci that, after being filtered and analyzed, were used to design 36 primers with perfect repeat motifs. Of these, 17 primers from microsatellite regions with tri-, tetra- or pentanucleotide repeats had their amplification tested in an optimization step. We successfully developed six primers of microsatellite loci, three tetranucleotide primers, two trinucleotides and one pentanucleotide, all classified as perfect. This selection sought accuracy and stability in genotyping by establishing a set of robust markers for population genetics studies.